The Exploratory Orientations of the Brain and Correlated with the Performance of Some Tennis Skills for Students - Rawaa Allawi Kadhim (Journal of Global Pharma Technology, 2018)
The exploratory orientation of the brain is an important self-motivation. The importance of this motivation is attributed to its obvious impact on the learning process because it enables learners to learn more about themselves, their abilities and their learning environment and to support them in persevering in the search for knowledge. The researchers noted the lack of interest by students motivated by the exploratory directions of the brain and the desire to keep pace with the wide changes in different areas of learning and knowledge and the relationship of that motivation results in their skilled performance, So deliberately researchers to study the trends of exploratory brain students and its relationship to the results of the performance of some skills in the game of tennis. The aim of the research was to identify the exploratory orientations of the brain and the technical performance of the sample of the students of the third stage of the morning study in the Faculty of Physical Education and Sports Sciences at Babylon University for the academic year 2016-2017. The researchers used the descriptive approach in their methods of surveying and correlative studies to suit the nature of the problem. The research community identified the students of the third stage of the morning study in the Faculty of Physical Education and Sports Sciences at Babel University for the academic year 2016-2017 (96), while the sample size (50) (52,083) were randomly selected by lottery. To achieve the objectives of the research, the researchers used the measure of the exploratory directions of the brain designed by the researcher (Maha Hadi Hussein) and the equivalent of (30) paragraphs, as well as the use of technical performance tests for tennis skills covered by the research and concluded the following: There is a significant correlation between the exploratory attitudes of the brain in the research sample of the students and their performance of some of the technical skills in the game of tennis.Keywords: Exploratory orientations, Brain and tennis skills.